1992
DOI: 10.1136/bjo.76.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence of the crystalline lens in early and late onset diabetes.

Abstract: Blue/green autofluorescence (excitation around 420 to 430 nm, emission around 520 nm) ofthe crystalline lens has been studied by an in vivo photographic method in two populations of diabetics and controls. The populations consisted of a geographically based survivor group of 161 mixed early and late onset diabetics (and 133 non-diabetic controls) and a second group of 104 early onset insulin dependent diabetics (and 138 non-diabetic controls), the latter all with non-cataractous lenses.Powerful associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…23,[45][46][47][48][49] Furthermore, within the diabetes patient population, lens fluorescence is also correlated with the development of the diabetes-related pathologies of cataract and retinopathy [50][51][52] and with systemic pathologies.…”
Section: Clinical Studies Of Lens Autofluorescencementioning
confidence: 99%
“…23,[45][46][47][48][49] Furthermore, within the diabetes patient population, lens fluorescence is also correlated with the development of the diabetes-related pathologies of cataract and retinopathy [50][51][52] and with systemic pathologies.…”
Section: Clinical Studies Of Lens Autofluorescencementioning
confidence: 99%
“…Over an extended period of time, low grade myopia may develop secondary to an increase in lens thickness and change in the curvature of the lens surface in metabolically stable adult diabetic patients. [1][2][3][4] Transient refractive changes associated with changing plasma glucose concentrations are well recognized features of DM. It has been reported that hyperglycemia may lead to the development of myopia, while hypoglycemia may result in the development of hyperopia.…”
mentioning
confidence: 99%
“…A previous study also found associations between retinopathy and lens fluorescence in eyes with clear lenses in both early-and late-onset diabetes [4]. However, it was not population-based and did not include information about metabolic control or use a referenced method of retinopathy grading.…”
Section: Discussionmentioning
confidence: 99%
“…Lens fluorescence has been shown to increase with age [3], duration of diabetes [3,4], glycaemia [5] and smoking [6]. The presence of retinopathy in a clinic-based population of patients with variable diabetes duration and type has been found to be associated with higher levels of fluorescence measured by a method not correcting for intrinsic light absorption [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation